Protective Actions of Acidic Hydrolysates of Polysaccharide Extracted From Mactra veneriformis Against Chemical-Induced Acute Liver Damage - Wang, Lingchong; Yang, Ying; Tan, Hor-Yue; Li, Sha; Feng, Yibin (Frontiers in Pharmacology, 2020)
The present study aimed to explore hepatoprotective effects of acidic hydrolysates (Ah-MVPS) of polysaccharide extracted from the marine clam M. veneriformis against ethanol- and CCl4- induced liver damages. Moreover, we also seek to probe the mechanism associating with liver protection of Ah-MVPS. A series of animal and cell experiments have been executed to detect suiting serological and histological indicators of hepatic tissues. Ah-MVPS can significantly reduce liver damages by means of an increase in hepatocyte superoxidase dismutase and inhibiting leakages of alanine aminotransferase and aspartate transaminase, as well as alleviation of malondialdehyde. Ah-MVPS inhibited steatosis and water-like hepatic deterioration in histological examination. It can suppress membrane destruction in boundaries and collapse of reticular scaffolds of the injured mice hepatocytes, and obviously reduce inflammatory extent of liver tissue aroused by overdose intake of ethanol or CCl4. In cell assays, Ah-MVPS markedly elevated the viability of L-02 cells exposed to an intoxication of ethanol or H2O2. The valuable effect of the Ah-MVPS might be, at least in part, because of ameliorating peroxidation or oxidative stress. Taken together, our findings reveal that Ah-MVPS offers a choice developed as protective agent to extenuate acute liver injures.